An Aldehyde‐Azomethine Imine [3+2]‐Cycloaddition: High‐Yielding Regioselective Synthesis of Substituted N, N‐Bicyclic Pyrazolidinones. Issue 27 (20th July 2018) - Gujral, Jagjeet; Reddy, T. Prabhakar; Gorachand, B.; Ramachary, Dhevalapally B.
Abstract: An enolate mediated aldehyde‐azomethine imine [3+2] cycloaddition of various aldehydes with N, N ‐cyclic azomethine imines is reported under DBU or t BuOK‐catalysis. High reaction rate, ease of operation, simple catalyst, easily accessible starting materials and a wide substrate scope with numerous applications make this reaction an ideal addition to the click chemistry. Abstract : An enolate‐mediated t BuOK‐catalysed aldehyde‐azomethine imine [3+2]‐cycloaddition of various aryl acetaldehydes with azomethine imines is reported. It is an efficient new catalytic click reaction for the synthesis of medicinally important substituted N, N ‐bicyclic pyrazolidinones in good yields and selectivity.